Oak decaying wood harbors taxonomically and functionally different bacterial communities in sapwood and heartwood. (April 2021) - Mieszkin, S.; Richet, P.; Bach, C.; Lambrot, C.; Augusto, L.; Buée, M.; Uroz, S.
Abstract: Wood decay is an important process in forest ecosystems, which relies on wood chemical properties and the action of a complex community of decomposers. While the important role of fungi in this process is recognized, our knowledge concerning the colonization of decaying wood by bacteria, their relative distribution as well as their potential functional roles remain under-investigated. In this context, our aim was to characterize how the bacterial communities are structured at both taxonomic and functional levels along the soil-wood continuum, using oak discs positioned on the forest floor for nine months. Using a combination of culture-dependent and -independent methods associated to a physical measure of wood decay, we evidenced that at the middle stage of decay investigated, the heartwood- and sapwood-inhabiting bacterial communities significantly differed from one another in term of richness and taxonomic composition, but also from those of the bulk soil. The functional screening revealed low metabolic potentials and a higher frequency of cellulose decomposing bacteria in wood than in the bulk soil, suggesting an adaptation of these communities to this habitat and to the physical-chemical conditions occurring in decaying wood. Together, our data evidence that the colonization of decaying wood by bacteria is based on a deterministic process linking extrinsic and intrinsic factors. Highlights: Lower metabolic potentials of bacteria inhabiting decaying wood compared to soil bacteria. Higher frequency of cellulose decomposing bacteria in wood than in the bulk soil. Muciliginibacter strains, isolated from wood, were efficient to hydrolyze cellulose. Luteibacter strains, isolated from wood, were efficient to hydrolyze chitin.